2017
DOI: 10.1038/ncomms14360
|View full text |Cite
|
Sign up to set email alerts
|

FAK signalling controls insulin sensitivity through regulation of adipocyte survival

Abstract: Focal adhesion kinase (FAK) plays a central role in integrin signalling, which regulates growth and survival of tumours. Here we show that FAK protein levels are increased in adipose tissue of insulin-resistant obese mice and humans. Disruption of adipocyte FAK in mice or in 3T3 L1 cells decreases adipocyte survival. Adipocyte-specific FAK knockout mice display impaired adipose tissue expansion and insulin resistance on prolonged metabolic stress from a high-fat diet or when crossed on an obese db/db or ob/ob … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 62 publications
6
51
0
Order By: Relevance
“…A study demonstrated FAK-mediated monocyte adhesion to endothelial cells by up-regulating VCAM-1 induced by ox-LDL (Yurdagul et al, 2016), which is consistent with our experimental results, the expression of VCAM-1 and ICAM-1, and activation of FAK were increased in HUVECs under ox-LDL stimulation in vitro, pretreated with Rg3 in ox-LDL stimulated HUVECs significantly suppressed FAK activation and VCAM-1 and ICAM-1 expression in a dose-dependent manner, indicating that Rg3 may play a role in protecting endothelial function by repressing FAK activation. Furthermore, FAK is highly conserved during evolution and widely expressed in different cells, FAK protein levels are increased in adipocytes of insulin-resistant mice which relate to adipose tissue expansion, leading to obese (Luk et al, 2017), FAK also can be activated by TNF-a in vascular smooth muscle cells which is involved in the process of atherosclerosis restenosis (Yu et al, 2018), suggesting that activation of FAK may increase not only in abnormal vascular endothelial cells and smooth muscle cells, but also in whole aorta of atherosclerotic ApoE −/− mice (Chen et al, 2018). In this study, activation of FAK was remarkable increased in gross aorta of ApoE −/− mice, while the ICAM-1 and VCAM-1 expression were increased mainly derived from vascular endothelium, and study confirmed that ICAM-1 and VCAM-1 were the endothelial-derived ligands may recruit monocytes, dendritic cells, T cells by binding to the integrin very late antigen-4 and lymphocyte function-associated antigen-1 expressed in these immune cells (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated FAK-mediated monocyte adhesion to endothelial cells by up-regulating VCAM-1 induced by ox-LDL (Yurdagul et al, 2016), which is consistent with our experimental results, the expression of VCAM-1 and ICAM-1, and activation of FAK were increased in HUVECs under ox-LDL stimulation in vitro, pretreated with Rg3 in ox-LDL stimulated HUVECs significantly suppressed FAK activation and VCAM-1 and ICAM-1 expression in a dose-dependent manner, indicating that Rg3 may play a role in protecting endothelial function by repressing FAK activation. Furthermore, FAK is highly conserved during evolution and widely expressed in different cells, FAK protein levels are increased in adipocytes of insulin-resistant mice which relate to adipose tissue expansion, leading to obese (Luk et al, 2017), FAK also can be activated by TNF-a in vascular smooth muscle cells which is involved in the process of atherosclerosis restenosis (Yu et al, 2018), suggesting that activation of FAK may increase not only in abnormal vascular endothelial cells and smooth muscle cells, but also in whole aorta of atherosclerotic ApoE −/− mice (Chen et al, 2018). In this study, activation of FAK was remarkable increased in gross aorta of ApoE −/− mice, while the ICAM-1 and VCAM-1 expression were increased mainly derived from vascular endothelium, and study confirmed that ICAM-1 and VCAM-1 were the endothelial-derived ligands may recruit monocytes, dendritic cells, T cells by binding to the integrin very late antigen-4 and lymphocyte function-associated antigen-1 expressed in these immune cells (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data have already established that O-GlcNAc modification has a critical role in the progress of human diseases, and particularly diseases such as cancer, diabetes, and Alzheimer's (7). Intriguingly, FAK has been associated with insulin resistance in adipocytes in the early stages of type II diabetes (48,49) and has also been implicated in the deposition of ␤-amyloid plaque (50,51). It would be reasonable to assume that dynamic regulation of FAK O-GlcNAcylation with phosphorylation may partially serve as a possible explanation for a number of diseases.…”
Section: Fak Was Modified By O-glcnacmentioning
confidence: 99%
“…For the insulin tolerance test (ITT), the mice were fasted for 6 h followed by IP injection of human insulin (0.75 units/kg; Novo Nordisk). For ZVAD treatment, ZVAD (6 mg/kg; catalog #187389-52-2; Calbiochem) was administrated IP every 2 days for 5 weeks as previously described (19). For fat transplantation, 12-weekold wild-type (WT) donor mice were sacrificed with an overdose of pentobarbital (150 mg/kg body weight), and sWATs were collected for transplantation.…”
Section: Animal Studiesmentioning
confidence: 99%